Supply Chain Partnership Success - Venter, Eugene (My University, 2011)
Customer service has become a crucial part of the integrated supply chain in the ICT industry. Customer-facing activities are often outsourced to authorized third party companies who, in effect become the custodians of customer satisfaction. The need for good customer service management has become a key differentiator for companies seeking competitive advantage. Furthermore, switching costs have reduced significantly and this is providing customers who have experienced poor service with a number of alternatives. This has increased the risk of outsourcing customer service. ICT companies are therefore faced with the challenge of developing successful partnerships with the purpose of mitigating potential risks, while maintaining high levels of customer satisfaction. The purpose of the study is to determine what factors will improve the likelihood of partnership success and to understand how these partnership success drivers can be incorporated into service level agreements (SLA). In-depth, semi-structured interviews were used to obtain the views of senior managers and executives involved in the management and outsourcing of customer service activities. The main finding was that service supply chain partnership success will be realised when end consumer satisfaction is achieved. In addition, collaboration, cooperation, coordination, communication and commitment and trust, will improve the likelihood of achieving partnership success. Finally it was found that these partnership success drivers can be incorporated into a service level agreement either explicitly or implicitly
MBA - WBS
Keywords: Supply chain partnerships; Service level agreements; ICT industry